From heritage to testimony: the “In Between?” project and the memory of the republican exile - González Vázquez, David; Conesa Sánchez, Ricard; Guixé Corominas, Jordi (Hispania Nova, 2021)
The continuous development of new technologies; a patrimonial policy focused on places of memory of the Spanish republican exile and the development of new international networks that promote projects linked to collective memory in Europe; has allowed new collaborative experiences to emerge; such as the “In Between?”. Promoted by the European Network Remembrance and Solidarity (ENRS) and aimed at young students from all over Europe; one of the editions of this project was carried out on the Franco-Spanish border. Different students of different nationalities shared an experience of research and data collection from various memorial spaces and testimonies of the Spanish republican exile; a memory that has forever marked different municipalities around the border; creating a unique identity.